Do significant risk warnings in annual reports increase corporate bond credit spreads? Evidence from China - Xi Gao; Wang Xiongyuan; Furong Tian (China Journal of Accounting Research, 2019)
Based on listed companies issuing bonds on the Shanghai and Shenzhen Stock Exchanges from 2007 to 2017, this study analyzes the relationship between significant risk warnings in Chinese companies' annual reports and corporate bond credit spreads. The main findings are as follows. First, in the Chinese market, "substantial warnings of significant risks" can significantly improve corporate bond credit spreads, reflecting the risk-warning effect; second, state-owned property rights weaken this effect, which only pertains to listed companies with poor risk management and low information quality; third, significant risk warnings increase investors' heterogeneous beliefs, also affecting credit spreads; and fourth, through textual analysis, it is found that the corporate bond credit spread is greater when the disclosed risk factors are more pessimistic and less similar to those of the previous year. The findings of this paper help to enrich the literature on credit spreads and risk disclosure.
Keywords: 650; Credit spreads; Risk disclosure; Risk warning